Purification of Geobacillus thermodenitrificans thermostable lipase / Nik Raikhan Nik Him and Muhammad Syafiq Abu Hassan - Nik Him, Nik Raikhan; Abu Hassan, Muhammad Syafiq (Universiti Teknologi MARA, 2024)
The demand for a structured method in producing high quality lipases has tremendously increased lipase purification technology within specific range of its original function. Crude lipase enzyme produced by a locally isolated Geobacillus thermodenitrificans (LGT) has demonstrated a notable potential for various bio-deinking capacities and other enzymatic actions based on the credential amount used. The enzyme production was set up in an airlift fermenter system using a cultivation medium prepared from (w/v) 1.25% glucose and yeast extract, 0.75% NaCl and 0.10% olive oil. Fermentation was accomplished in 24 hours with an air flow rate of 1.00 L/min. Physical parameters were maintained at 7.0% (v/v) inoculum size and pH 6.8. The extracted extracellular crude lipase was purified to homogeneity using four-step procedures. The acetone precipitation, Sephadex G-100 filtration chromatography and double steps of DEAE Sefarose CL-6B anion with exchange chromatography has resulted in a final yield of 25.00%. The molecular weight of the purified enzyme was estimated to be 33.5 kDa using an SDS-PAGE analysis. The lipase enzyme has a high potential to be further used for many industrial purposes and has been purified with 22.1-fold protein. The above functional reported characteristics of the LGT was considered a modest quality taking into consideration of its ability to stand high temperature range.